Socio-Cultural Aspects of Modern Environmental Risk Management (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article explores the socio-cultural dimensions of environmental risk management in the context of contemporary ecological challenges. It highlights how cultural values, traditional knowledge, and social norms influence communities’ perceptions of environmental risks and their response strategies. The study emphasizes the need to integrate local cultural practices into environmental policy-making to ensure sustainable and effective outcomes. By analyzing case studies and theoretical insights, the article underscores the importance of interdisciplinary approaches that include sociology, anthropology, and environmental science. The findings suggest that culturally informed strategies can significantly enhance community engagement and resilience in managing environmental risks.